The Superficial Inferior Epigastric Artery Fascia Flap in Rats - Saffari, Tiam M.; Bishop, Allen T.; Shin, Alexander Y. (Journal of Reconstructive Microsurgery Open, 2020)
Background An adipofascial flap in the rat may provide new options for adding vascularization to scarred or nonvascularized beds for a variety of research studies. Current literature lacks sufficient description for a simple reproducible flap model for a vascularized pedicled flap in rats, in particular for neovascularization of allograft nerves for the reconstruction of sciatic nerve defects. The purpose of this study was to describe a surgical technique and determine long-term survivability for the pedicled superficial inferior epigastric artery fascial (SIEF) flap in the rat to meet requirement for a tunneled adipofascial flap to add vascularization to the sciatic nerve area.Methods The technique and use of a 4 × 3-cm SIEF flap are described. Twenty Lewis rats underwent the technique to determine feasibility. The flap was wrapped around processed allograft nerve reconstructions and viability of the flap was evaluated after 12 and 16 weeks. To visualize vessels, nerve grafts were harvested at 12 weeks and stained with hematoxylin-eosin and an antibody against microvessels (CD-34).Results All flaps remained viable after survival of 12 and 16 weeks. Complications included one hematoma formation and two lymphocele formations that did not have any impact on the flap. Immunohistochemistry confirmed an increase in microvessels and Schwann cell nuclei in the SIEF group compared with nerve samples from the unoperated, contralateral side.Conclusion A pedicled adipofascial flap model in the rat to provide a vascular bed for sciatic nerve reconstruction is detailed with long-term survivability evaluation of the flap. This flap is technically simple to be harvested and is suitable for revascularization procedures of various tissues in the lower abdomen, genital area, thigh, or upper limb of the rat.
Keywords: sciatic nerve vascularization; vascularized bed; pedicled flap; animal models